Rancang Bangun Sistem Manajemen Proyek pada PT Gentraco Buana Utama Palembang - Donna Agnesia Chandra; Desi Pibriana (Universitas Multi Data Palembang, 2026)
Information technology advancements drive construction companies to enhance efficiency through computerized systems. PT Gentraco Buana Utama faces data management challenges due to manual processes using Excel and WhatsApp, leading to scheduling overlaps and delayed progress reporting. This research aims to develop a web-based project management system to integrate operations, scheduling, and structured project monitoring. The development follows an iterative model consisting of recurring phases: planning, analysis, design, implementation, and testing. The system is built using the Laravel framework and MySQL database. The results demonstrate that the system successfully centralizes project data, provides real-time monitoring via Gantt Chart visualizations, and features automated progress summaries. These features improve data accuracy and evaluation speed for both management and clients.